Influence of dietary 1Î±lpha-hydroxycholecalciferol, individually or in combination with microbial phytase in calcium and phosphorus deficient diets on growth performance and tibia parameter of Japanese quails (Coturnix japonica) (Acta Scientiarum. Animal Sciences, 2018)
The effect of 1Î±-OH-D3 in calcium-phosphorus (Ca-P) deficient diets on Japanese quail growth performance and tibia parameters was investigated. Eight-day-old (n = 160) newly hatched quails were weighed and randomly allocated to 20 groups, each with 4 replicate pens of 8 birds. Treatments were as follows: T1, Ca-P-adequate; T2,Ca-P-deficient; T3, Ca-P-deficient + 500 FTU kg-1 of phytase (Ph); T4, Ca-P-deficient diet + 5 µg kg-1 of 1Î±-OH-D3; T5,Ca-P-deficient + Ph + 5 µg kg-1 of 1Î±-OH-D3. Results showed that quails fed Ca-P-adequate had significantly higher body weight compared with quails fed Ca-P-deficient, Ca-P deficient supplemented with 1Î±-OH-D3 and Ca-P-deficient supplemented with 1Î±-OH-D3 and phytase, but did not differ from Ca-P-deficient diet supplemented with phytase. Quails fed Ca-P deficient were unable to achieve FCR comparable to quails fed Ca-P-adequate (p < 0.05). The percentage of bone ash data indicated that quails fed Ca-P-adequate had higher tibia ash compared with other groups except for quails fed Ca-P deficient diet supplemented with combination of 1Î±-OH-D3 and phytase. Quails fed Ca-P-adequate had higher tibia P compared with quails fed Ca-P-deficient. In conclusion, these results indicated that quails fed Ca-P-deficient supplemented with 5 µg kg-1 of 1Î±-OH-D3 in combination of 500 FTU kg-1 of phytase were able to achieve the same tibia ash and Ca compared with quails fed Ca-P-adequate.